2015
DOI: 10.1186/s12879-015-1045-2
|View full text |Cite
|
Sign up to set email alerts
|

High burden of STI and HIV in male sex workers working as internet escorts for men in an observational study: a hidden key population compared with female sex workers and other men who have sex with men

Abstract: BackgroundMale sex work in the western countries has changed, including now a subculture of male sex workers who have paid sex with men arranged for via the internet. The men involved in this subculture do not easily identify themselves as sex workers nor as homosexual, and are therefore missed by regular health care and public health interventions. These male sex workers may form a hidden key population for sexually transmitted infections (STIs) and HIV, bridging towards other persons outside this context.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 21 publications
8
47
0
Order By: Relevance
“…As already described, if considering subjects at high risk for STI transmission, such as sex workers or MSM with multiple sexual partners, CT infection prevalence can easily exceed 10-15 % (Petrovay et al, 2009;Mejuto et al, 2013;Yang et al, 2014;Verhaegh-Haasnoot et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As already described, if considering subjects at high risk for STI transmission, such as sex workers or MSM with multiple sexual partners, CT infection prevalence can easily exceed 10-15 % (Petrovay et al, 2009;Mejuto et al, 2013;Yang et al, 2014;Verhaegh-Haasnoot et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…age [22], education [22]), individual risk factors (e.g. condomless anal intercourse [4,22,36], HIV knowledge [22], sexually transmitted infections (STI) history [52,53], higher number of sexual partners [1,2], substance use [54]), and social level factors (e.g., forced sex, harassment and violence [1,2,4,36]). Alternately, social cohesion among MSM who sell sex has been identified as a protective factor [3].…”
Section: Introductionmentioning
confidence: 99%
“…(35,36). Additionally, MSW may not identify as sex workers nor perceive themselves to be at risk of HIV and other STIs (3,34,37). These factors may account for the low testing norms, low selfefficacy and poor uptake of HIV testing we observed.…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya, a study found low prevalence (26%) of recent HIV testing among MSW(33). Work done in the Netherlands also found that majority of MSW (63%) reported no recent history of HIV or STI testing compared with compared to 32% FSW and 35% MSM(34). MSW are hidden key sub-population largely invisible to HIV programs(34).…”
mentioning
confidence: 99%
See 1 more Smart Citation